Incidence of atrioventricular block after isolated coronary artery bypass grafting: a systematic review and pooled-analysis - Ramin Yaghoobian; Reza Hosseini Dolama; Reza Hosseini Dolama; Hamidreza Soleimani; Sahar Saeidi; Mahtab Mashayekhi; Parsa Mirzayi; Ghazaal Alavi Tabatabaei; Kaveh Hosseini; Kaveh Hosseini (Frontiers in Cardiovascular Medicine, 2023)
Background and objectivesAtrioventricular block (AVB) is a serious complication following coronary artery bypass grafting (CABG) surgery, and its high-grade form may necessitate the implantation of a permanent pacemaker (PPM). AVB is associated with increased morbidity and mortality rates. This study aims to estimate the incidence of AVB and subsequent PPM implantation after isolated CABG surgery.Material and methodsWe searched electronic databases of PubMed, Embase, and Scopus from inception to 18 November 2022. Clinical trials and observational studies reporting the incidence of post-CABG AVB or subsequent PPM implantation in adult patients were included. The total incidence for all included outcomes was calculated using the inverse variance method, and the I2 statistic was reported to evaluate the heterogeneity of studies.ResultsA total of 28 studies met the inclusion criteria. Four studies [3 cohorts, 1 randomized controlled trial (RCT)] reported AVB without specifying its type; one (cohort) reported different degrees of AVB, 20 (12 cohorts, 8 RCTs) reported complete heart block (CHB) (or AVB requiring temporary pacing), and nine (8 cohorts, 1 RCT) reported the number of PPM inserted due to AVB. The pooled incidence of AVB, CHB (or AVB requiring temporary pacing), and PPM due to AVB was 1.16%, 1.73%, and 0.58%, respectively. Meta-regression analysis revealed that age, gender, diabetes, hypertension, hyperlipidemia, or smoking were not significantly associated with AVB, CHB, or PPM implantation.ConclusionThis study highlights the incidence of AVB and the need for PPM implantation following CABG surgery. The findings emphasize the importance of postoperative monitoring and surveillance to improve patient outcomes. Systematic Review Registrationhttps://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022377181, identifier PROSPERO CRD42022377181.